School-travel by public transit: Rethinking active transportation - Christine Voss; Meghan Winters; Amanda Frazer; Heather McKay (Preventive Medicine Reports, 2015)
Background: Walking and cycling to school is a source of physical activity (PA). Little is known about public transit use for travel to school and whether it is a physically active alternative to car use for those who live too far to walk. Purpose: To describe school-trip characteristics, including PA, across travel modes and to assess the association between PA with walk distance. Methods: High school students (13.3 ± 0.7 years, 37% female) from Downtown Vancouver wore accelerometers (GT3X+) and global positioning systems (GPS) (QStarz BT-Q1000XT) for 7 days in October 2012. We included students with valid school-trip data (n = 100 trips made by n = 42 students). We manually identified school-trips and mode from GPS and calculated trip duration, distance, speed, and trip-based moderate-to-vigorous PA (MVPA; min). We assessed between-mode differences and associations using multilevel regression analyses (spring 2014). Results: Students accrued 9.1 min (±5.1) of trip-based MVPA, which was no different between walk and transit trips (p = 0.961). Walking portions of transit trips were similar to walking trips in terms of distance (p = 0.265) and duration (p = 0.493). Walk distance was associated with MVPA in a dose–response manner. Conclusions: Public transit use can contribute meaningfully toward daily PA. Thus, school policies that promote active school-travel should consider including public transit.